2015
DOI: 10.1017/s1751731115000622
|View full text |Cite
|
Sign up to set email alerts
|

Use of re-esterified palm oils, differing in their acylglycerol structure, in weaning-piglet diets

Abstract: Re-esterified oils are new fat sources obtained from chemical esterification of acid oils with glycerol (both economically interesting by-products from oil refining and biodiesel industries, respectively). The different fatty acid (FA) positional distribution and acylglycerol composition of re-esterified oils may enhance the apparent absorption of saturated fatty acids (SFA) and, thus, their overall nutritive value. The aim of the present study was to investigate the potential use of re-esterified palm oils, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…This means that TAG and DAG were almost completely hydrolyzed along the gastrointestinal tract, and MAG were absorbed due to their hydrophilic character (2-MAG and some 1(3)-MAG) or completely hydrolyzed to glycerol and FFA (mainly 1(3)-MAG). FFA constituted the major lipid fraction in feces for all treatments, suggesting that the formation of mixed micelles may be the rate-limiting step of fat absorption in fattening pigs, as has also been observed in weaning piglets (Jones et al, 1992;Vilarrasa et al, 2015), but less severely.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…This means that TAG and DAG were almost completely hydrolyzed along the gastrointestinal tract, and MAG were absorbed due to their hydrophilic character (2-MAG and some 1(3)-MAG) or completely hydrolyzed to glycerol and FFA (mainly 1(3)-MAG). FFA constituted the major lipid fraction in feces for all treatments, suggesting that the formation of mixed micelles may be the rate-limiting step of fat absorption in fattening pigs, as has also been observed in weaning piglets (Jones et al, 1992;Vilarrasa et al, 2015), but less severely.…”
supporting
confidence: 54%
“…However, the effect of FFA on UFA absorption is lower in comparison with that of SFA (Powles et al, 1993). Thus, acid palm oils may be an economically interesting alternative to native palm oils, provided they have a moderate amount of FFA and a low percentage of moisture, impurities and unsaponifiable matter, as we have also observed in weaning piglets (Vilarrasa et al, 2015).…”
Section: Digestibility Balancementioning
confidence: 53%
See 2 more Smart Citations
“…Moreover, Vilarrasa et al (2015b) reported that the substitution of 60 g/kg re-esterified palm oil by re-esterified SO or a 25:75 combination of both, improved F:G without affecting ADG or ADFI of broilers from 0 to 41 d of age. In a second paper, Vilarrasa et al (2015c) reported similar results in weanling pigs fed diets with 100 g/kg of native or re-esterified palm oil. The authors had not found any report comparing these two re-esterified lipid sources in broilers.…”
Section: Growth Performance Experiments 1 Andmentioning
confidence: 61%